THE TRADITION OF PUBLIC CRITISM IN THE LAPOR PAK PROGRAM (Analysis of the Spiral of Silence Jokes of Comedian Criticism) - Fitransyah, Fitransyah; Aswan Aswan (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
This research discusses the tradition of public criticism in the Lapor Pak program by looking at the spiral of silence towards comedian jokes. This study aims: to find out the forms of public criticism in the Lapor Pak program; the relationship between comedian criticism jokes and the people’s voice or public opinion. The type of research used is descriptive qualitative using mass communication theory, namely The Spiral of Silence as a research approach. As for the data obtained from listening to and watching videos or Lapor Pak scenes uploaded by the official trans 7 youtube channel and supporting data in the form of articles, journals and netizen comments. The results of this study indicate that public criticism in Lapor Pak has become a bait in every episode because it is always done by the players. As for criticism expressed in the form of jokes which are presented in two forms, there are dialogues and monologues. And critical jokes always depart from a case that is viral of widely discussed in society so that in this case we can conclude that jokes represent the voice of the people or existing public opinion.